Branding Strategy For Social Media - Muhammad Yusuf AR; Eka Hendrayani; Shadli Rolaskhi; Sopi Pentana; Pitono Pitono (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
MSMEs are supporting the nation's economy, however, some MSME actors still experience various difficulties in running a business. One of them is the difficulty in the field of marketing, in the current era of social media marketing development, several micro, small and medium enterprises, especially in the Majalaya sub-district, are facing difficulties keeping up with the times in terms of product marketing. From the survey that has been conducted, MSME actors in the Majalaya sub-district admit that they have difficulties in marketing their products and developing markets. This is due to the product's lack of awareness of the branding of MSME products where MSME actors do not highlight the identity and superiority of the products offered, thus reducing the interest of potential consumers to buy these products. As a solution to the problem above,mConduct dedication in the form of education and training regarding product branding in social media marketing.